Pemanfaatan Media Informasi Komisi Komunikasi Sosial â€œKOMSOSâ€ Sebagi Pusat Informasi Terhadap Masyarakat Gereja Khatolik Kota Padang - Monang Aditya Sitanggang; Defhany Defhany (Jurnal Ilmu Komunikasi Dan Media Sosial (JKOMDIS), 2023)
This research is motivated by advances in social media technology that provide many good benefits in life. In addition to the good benefits, technological advances also have a negative effect on the social environment. The impact of social media makes a person do not care about the people around him, is indifferent, lacks attention which can change the pattern of life that is around us and also change the communication patterns that exist within the scope of society, especially the Catholic community of Padang city. Modern technology has been widely used by Catholics as a medium for meeting the information needs they need. Along with the development of technology, utilization through modern social media puts forward an effectiveness in the search for information. Social media has become a new digital space that is of great interest to all circles. The presence of social media has changed and shifted all aspects of people's lives who use social media. Now society is in a very fast flow of change due to social media. Social media is a channel or means of socializing online in cyberspace (the internet). As a medium of communication, social media is in great demand by the public because of the convenience and features it offers. Now social media is growing very rapidly as evidenced by the presence of various kinds of social media such as Facebook, Twitter, You Tube, Instagr, Line, and others. It is unavoidable that the existence of social media provides many conveniences to its users. The church is facing current trends These media make it easy for users to post and access and are used as opportunities for evangelism and worship. Almost every second we can easily access the gospel message, sermons, testimonies, praise and worship.